Job Satisfaction among Nursing Staff - Hewa Saleh, (Iraqi National Journal of Nursing Specialties, 2023)
Objectives: The specific objectives of the present study were to assess the level of job satisfaction amongnursing staff who are working in the Ministry of Health and Ministry of Higher Education and ScientificResearch in the provinces of Erbil, Mosul and Kirkuk to determine the factors that affect their satisfaction.Methodology:٨descriptive design was carried-out from September 20, 2006 through April 1,'؛ 2007 in orderto assess the job satisfaction for nursing staff in governmental health agencies and educational setting.Quantitative research methods were utilized to employ the study design. The study was conducted on three Iraqigovernorates (Mosul, Kirkuk, and Erbil). The sample of the study was collected from all teaching hospitals andsome of Primary Heath Care Centers, Faculties and institutions of Nursing, as well as, administrative staff inDirectorates of Health in the above mentioned provinces. A random sample of (547) nurse participated to answerthe study questions. Those nurses had been chosen randomly from the three provinces. Through extensive reviewof relevant literature, and a questionnaire was constructed for the purpose of the study. It was consisted of threemajor parts and the overall items included in the questionnaire were (78). Content validity was determined forthe questionnaire. It was presented to a panel of (20) expert.Results: The analysis of data shows that the majority of the sample (83.19%) was dissatisfied with their job.Also, it revealed that Kirkuk’s Nurses were more dissatisfied than Mosul and Erbil Nursing staff.Recommendation: The study recommended that the health administration should acknowledge the profession ofNursing. There is a need for all nurses' work to be acknowledged by administration nurses need some form ofappreciation or recognition for their hard work. As nurse managers are that part of administration that arecommunicating with nurses, most on a ward level, it will be necessary to assist them to develop skills so that therecognition that nurse needs can be satisfied